Assessment of polyanion (BF4− and PF6−) substitutions in hybrid halide perovskites. Issue 17 (31st October 2014) - Hendon, Christopher H.; Yang, Ruo Xi; Burton, Lee A.; Walsh, Aron
Abstract : The incorporation of tetrafluoroborate and hexafluorophosphate in halide perovskites is found to result in substantial band gap widening. Abstract : Halide perovskites have attracted attention for light-to-electricity conversion in solar cells due to their favorable optoelectronic properties. In particular, the replacement of the A cation by an isovalent molecule has proven highly successful. We explore the substitution of the X anion, producing polyanion perovskites based on hexafluorophosphate and tetrafluoroborate. Starting from CsPbI3, the effect of partial and complete substitution is investigated using relativistic electronic structure calculations. BF4 − results in a larger perturbation to the electronic structure than PF6 − ; however, both localise the band edge states, and the end member compounds are predicted to be wide band gap dielectrics.